Effects of high dose oral creatine supplementation on anaerobic capacity of elite wrestlers - Kocak, S.; Karli, U. (The Journal of Sports Medicine and Physical Fitness, 2003)
Aim: The purpose of this study was to investigate the effect of high dose oral creatine supplementation on anaerobic capacity of elite wrestlers. Methods: Experimental design: comparative randomized design. Setting: Wingate anaerobic tests of the participants were taken at the Human Performance Laboratory of the Department of Physical Education and Sports in The Middle East Technical University, Ankara, Turkey. Participant: 20 active international level wrestlers participated (22 to 27 years old). Interventions: the daily dosage of creatine or placebo was divided into 4 equal amounts (5 gx4 = 20 g). Every 5 g of supplement was dissolved in 250 ml water and it was given to participants 1 hour before breakfast, lunch, dinner, and workout session. Measures: subjects underwent a 30-s Wingate Anaerobic tests until exhaustion in pre- and post-tests. After the pretest measurements were completed, participants were classified as creatine (Cr., n=10) and placebo (Pl., n=10) groups with regard to their average anaerobic power scores obtained during the test. Results: Results of paired ''t''-test revealed that there was no significant change in placebo group between pre- and post-test in average and peak anaerobic power. However, average and peak power mean scores obtained from post-test (8.123±0.448 W/kg and 10.523 ±1.004 W/kg) were significantly (p<0.01) higher than pretest (7.233±0.483 W/kg and 8.992± 0.665 W/kg) for creatine group. Results of the independent ''t''-test also indicated that the mean gained scores of creatine group in average and peak power were significantly higher than placebo group (p<0.01). Conclusion. This study demonstrates that short-term high dose oral creatine supplementation has an ergogenic effect on anaerobic capacity of elite wrestlers